Electronics training using microcontroller at MA Ihyaul Islam Bolo - Astutik, Rini Puji; Mas'ud, Arbi Alfian; Gunawan, Budy; Khakim, Khasanul (Community Empowerment, 2025)
This community service was conducted at Madrasah Aliyah Ihyaul Islam Bolo, Gresik, a school with the potential to develop skilled human resources in the industrial sector. This activity aimed to enhance students' knowledge and skills about the Internet of Things (IoT) technology for automatic control. The implementation method involved electronics training using the Arduino Uno microcontroller, including material presentation, demonstrations, case studies, and hands-on practice. A total of 20 twelfth-grade students participated in this training. The results achieved demonstrate an increase in students' understanding of the training material. Based on questionnaires completed after the training, 44% of students stated a good understanding of the material provided. In addition, there was a strong positive correlation (0.9) between students' assessment of the quality of the material and the completeness of the training material. This activity made a significant contribution to improving the competence of students and teachers related to IoT technology, as well as opening up opportunities for collaboration between schools, universities, and industry.